A Matrix Metalloproteinase-2-Based Nomogram to Assess the Risk of Encapsulating Peritoneal Sclerosis in Peritoneal Dialysis Patients. (19th January 2021) - Chou, Che-Yi; Tseng, Chin-Chung; Chen, Jin-Bor; Hung, Chin-Chuan; Huang, Chiu-Ching
Abstract : Background . Encapsulating peritoneal sclerosis (EPS) is a rare but serious complication of peritoneal dialysis (PD). So far, there is no biomarker-based prediction tool available for EPS. Matrix metalloproteinase-2 (MMP-2) is a protein involved in the breakdown of the extracellular matrix, and the effluent MMP-2 can be a potential biomarker of EPS. This study is aimed at developing a nomogram for EPS based on effluent MMP-2 levels. Patients and Methods . We enrolled 18 EPS patients and 90 gender-matched PD patients without EPS in this cross-sectional case-controlled study. The effluent MMP-2 levels and possible risk factors for EPS were analyzed using multivariable logistic regression, and a nomogram was developed. The nomogram was validated using 200 bootstrap resamples to reduce overfit bias. Results . The effluent MMP-2 levels in EPS patients were significantly higher than those in normal PD patients (p < 0.001, Manny-Whitney U test). Effluent MMP-2 levels and PD duration were independently associated with EPS risks (p < 0.001 and p = 0.001 ) in multivariate logistic regression. A nomogram based on MMP-2 levels and PD duration was proposed. The AUC of MMP-2 was 0.824, and the AUC of the nomogram was 0.907 (p = 0.05 ). Conclusion . A nomogram based on effluent MMP-2 levels and PD duration may predict EPS with high accuracy.